The New Atheism: Taking a Stand for Science and Reason - Victor J Stenger (Prometheus Books, 2009)
Stenger describes how secularists have jumped on the anti-Islam hysteria generated after September 11 to take the offensive against religion generally, most often the Abrahamic monotheistic religions of the West.